Goal-oriented Balancing - Lars-Johan Åge (Grounded Theory Review: An International Journal)
This study focuses on the substantive area of sales management and it suggests that the main concern of a sales manager is to reach the sales and economical goals of the sales organization. The social process by which this main concern is resolved is called goal-oriented balancing and it describes two complementary organizational dimensions, frame development and individual development that are continuously balanced against each other. That is, the sales manager must establish effective organizational processes and structures as well as find the keys to maximum individual performance. These two processes have to be in balance and supportive of each other.